2008
DOI: 10.1007/s11373-008-9259-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dopamine D2 receptor function in hypothalamus and corpus striatum: their role in liver, plasma and in vitro hepatocyte ALDH regulation in ethahol treated rats

Abstract: Dopamine D 2 receptors are involved in ethanol self-administration behavior and also suggested to mediate the onset and offset of ethanol drinking. In the present study, we investigated dopamine (DA) content and Dopamine D 2 (DA D 2 ) receptors in the hypothalamus and corpus striatum of ethanol treated rats and aldehyde dehydrogenase (ALDH) activity in the liver and plasma of ethanol treated rats and in vitro hepatocyte cultures. Hypothalamic and corpus striatal DA content decreased significantly (P \ 0.05, P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Among alcoholics, one small post-mortem study reported that higher impulsivity was associated with increased 5HT2A receptor binding (Thompson et al, 2012). In animal models, alcohol exposure has been associated with region-specific increases (Akash et al, 2008) and decreases (George et al, 2010) in 5HT2A receptors binding. Studies indicate that increased activity in 5HT2A-mediated pathways relative to 5HT2C activity increases cue response and impulsivity in rat models of cocaine addiction (Cunningham and Anastasio, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among alcoholics, one small post-mortem study reported that higher impulsivity was associated with increased 5HT2A receptor binding (Thompson et al, 2012). In animal models, alcohol exposure has been associated with region-specific increases (Akash et al, 2008) and decreases (George et al, 2010) in 5HT2A receptors binding. Studies indicate that increased activity in 5HT2A-mediated pathways relative to 5HT2C activity increases cue response and impulsivity in rat models of cocaine addiction (Cunningham and Anastasio, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of these alleles have also been reported to be higher in alcohol dependent persons than in the general population in other East Asians: Han Chinese in Taiwan , Koreans , and Japanese . The involvement of ALDH has been reported to differ from that of ADH in AD .…”
mentioning
confidence: 99%